(untitled) (مجلة إحالات, 2026)
This study aims to shed light on Doctor Mohammad Michbel’s rhetoric and critique of Moroccan , and his view to the relationship between rhetoric and literary genres, through our offer to read a group of researchers of his most prominent and most important works, and their approaches to his pioneering project through literature and research, on: Rhetoric of Rhetoric, Rhetoric and Narration, From minimalist rhetoric to broad rhetoric, rhetoric and literature; From pictures of language to images of discourse ... To conclude, with the features and characteristics that are the pillars and pillars of the Al-Mashbali project, which is basically based on the necessity of openness to various types of discourse, in order to break out of the dominance of literary rhetoric that is reduced to a new and distinct rhetoric with broad horizons.